Fundamentals of psychology - W. Eysenck, Michael (USA : Psychology Press, 2009)
"Aimed at those new to the subject, this clear and reader-friendly textbook combines an authoritative tone, a huge range of psychological material and an informal, analogy-rich style. It offers a balanced and accurate representation of the discipline through a highly accessible synoptic approach, which seamlessly brings together all the main approaches to psychology, including social, developmental, cognitive
Includes bibliographical references and index.
Keywords: psychology